The Multiperiod Information Content of Accounting Earnings: Confirmations and Contradictions of Previous Earnings Reports - Freeman, Robert N.; Tse, Senyo (Journal of Accounting Research, 1989)
Robert N. Freeman, Senyo Tse, The Multiperiod Information Content of Accounting Earnings: Confirmations and Contradictions of Previous Earnings Reports, Journal of Accounting Research, Vol. 27, Current Studies on The Information Content of Accounting Earnings (1989), pp. 49-79